A study on new product success of a multinational corporation in Asia Pacific region. - Chang, Michael Ching Woei. (2009)
New product development remains one of the riskiest yet most important management challenge. A better understanding of what makes a new product a success - what separates the winners from the losers - is essential to improve project selection and management. Successful new product launches will definitely help ensure continual corporate prosperity in this highly competitive and rapidly changing part of the world called Asia.